2017
DOI: 10.3847/1538-4357/aa862a
|View full text |Cite
|
Sign up to set email alerts
|

PHAT. XIX. The Ancient Star Formation History of the M31 Disk

Abstract: We map the star formation history across M31 by fitting stellar evolution models to color-magnitude diagrams of each 83″×83″ (0.3×1.4 kpc, deprojected) region of the Panchromatic Hubble Andromeda Treasury (PHAT) survey outside of the innermost 6 12 ¢´¢ portion. We find that most of the star formation occurred prior to ∼8 Gyr ago, followed by a relatively quiescent period until ∼4 Gyr ago, a subsequent star formation episode about 2 Gyr ago, and a return to relative quiescence. There appears to be little, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
147
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 102 publications
(162 citation statements)
references
References 57 publications
(104 reference statements)
11
147
0
Order By: Relevance
“…Several models have posited a major merger between M31 and (what would have been) the third largest member of the LG ∼2-4 Gyr ago (e.g., Hammer et al 2018;D'Souza & Bell 2018). These models can qualitatively explain some observed features of M31, such as a global burst of star formation 2-4 Gyr ago (e.g., Bernard et al 2015;Williams et al 2017) and the metal-rich inner halo. For example, D' Souza & Bell (2018) hypothesize such an interaction between M31 and M32p (the putative progenitor of M32) could explain the metal-rich component of M31's halo and the unusually compact nature of M32.…”
Section: Resultsmentioning
confidence: 99%
“…Several models have posited a major merger between M31 and (what would have been) the third largest member of the LG ∼2-4 Gyr ago (e.g., Hammer et al 2018;D'Souza & Bell 2018). These models can qualitatively explain some observed features of M31, such as a global burst of star formation 2-4 Gyr ago (e.g., Bernard et al 2015;Williams et al 2017) and the metal-rich inner halo. For example, D' Souza & Bell (2018) hypothesize such an interaction between M31 and M32p (the putative progenitor of M32) could explain the metal-rich component of M31's halo and the unusually compact nature of M32.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, Pezzulli et al (2015) measured the instantaneous mass and radial growth of the stellar disks of a sample of 35 nearby spiral galaxies that includes NGC 7793, finding clear signatures of its inside-out growth. Within the Local Group, the spatially resolved star formation history analyses of M31 from the PHAT survey (e.g., Williams et al 2017) and M33 (Barker et al 2007(Barker et al , 2011 have shown similar behaviors.…”
Section: Tablementioning
confidence: 97%
“…Therefore, we can only expect the C/M ratio to be a useful diagnostic if the stellar population spans the appropriate age range. Lewis et al (2015) and Williams et al (2017) estimated the spatially-resolved star-formation history (SFH) across the disk by fitting stellar evolution models to PHAT color-magnitude diagrams (CMDs). They find that there are global star formation events from ≈1.5-4 Gyr and at ages 8 Gyr.…”
Section: Agementioning
confidence: 99%